Analisis Peran Pendidikan Politik Dalam Membangun Kesadaran Mahasiswa Berpartisipasi Dalam Pemilu Tahun 2024 - Wawan Patriansyah; Nursiah Hasibuan; Muallim Hasibuan; Tri Eva Juniasih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Elections are a means to determine the fate of the nation for the next five years. For this reason, it is necessary to provide understanding through political education to the public, especially students who are classified as beginner voters with the aim of building student participation to participate in elections. As educators who have an important role in providing education in the field of politics to students, this research will analyze the role of political education in building student participation in elections. The aim of this research is to find out the role of political education in increasing student participation in the 2024 elections. The method used in this research is descriptive qualitative. The respondents or samples for this research were 120 FISIPOL UGN students. Based on the research results, it was concluded that students' understanding and knowledge of elections is still lacking due to the lack of political education provided. Student participation in taking part in the upcoming elections is in the good category, but still needs improvement because students' awareness of election participation is still limited to exercising their right to vote. Good education and students' low political attitudes will influence students' mindsets about things that can be followed in the implementation of elections.